(untitled) (World Bulletin of Social Sciences, 2022)
This research aims to instill leadership qualities from an early age. This research is deliberately done so that it is hoped that it will form a leadership spirit from an early age. This study uses the observation method. The results of this study indicate that there is a leadership spirit among these students to become a leader. The ability to become a leader is demonstrated very well by the students at State Elementary School 1 Telaga.